ON THE EDGE-BALANCED INDEX SETS OF PRODUCT GRAPHS - Krop, Elliot; Lee, Sin-Min; Raridan, Christopher (IndoMS, 2011)
We characterize strongly edge regular product graphs and find the edge-balanced index sets of complete bipartite graphs without a perfect matching, the direct product Ksubn/sub X Ksub2/sub. We also prove a lemma that is helpful to determine theedge-balanced index sets of regular graphs.DOI :Â http://dx.doi.org/10.22342/jims.0.0.20.71-78